MISMATCH ENGLISH EDUCATION IN INDONESIA - Bire, Jos (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 17 (2010): March 2010, 2010)
This writing aims at helping English teaches in Indonesia to view the objective outcome of English language education in Indonesia across the decades since the nation’s independence from the Dutch in 1945. It concentrates on data concerning objectives, content, methods of teaching and the evaluation of teaching/learning English as a foreign language across Senior High School curricula. The discussion emphasizes the evidence of mismatch in the four components of TEFL. Eight curricula are under critical investigation here in the research, except the most recent one namely the 2006 curriculum as it is at present being implemented. The discussion pinpoints a discovery where there has been a case of mismatch in terms of the implementation of English education process across the decades. This may in turn functions as a catalyst to guide and to empower English teachers in their future teaching/lesson plan.